Peran Perempuan dalam Politik Simbolis Pakubuwono X 1893-1939 M - Nila Zaqiatul Miskiyah; Nurul Baiti Rohmah (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
In Surakarta Sunanate, women became the determinant of strength, resilience, and success for the susuhunan in achieving political endeavors. Women as wives, empresses, queens, friends, children, courtiers, and ordinary people play an important role in Surakarta Sunanate. The purpose of this study is to determine the involvement of women in Pakubuwono X strategy in achieving the goals and political stability of Surakarta Sunanate 1893-1939 M. The involvement of women influenced the social and cultural system in the Sunanate. This research uses the historical research method. The research went through the stages of topic selection, source collection, verification (historical criticism), analysis and synthesis, and writing. The sources used are written documents from various library sources, journals, scientific research, articles, documentation, and various sources related to the discussion. The results showed that the birth of Pakubuwono X brought progress to Surakarta Sunanate. The progress and glory of Surakarta Sunanate did not escape from Pakubuwono X policy of involving women in political affairs. Pakubuwono X achievements cannot be separated from women who play an important role in government defense, economic improvement, educational progress, Sunanate characteristics, and preservation of cultural traditions. Keywords: Pakubuwono X; symbolic politics; role of women